Crp And Il-6 Of Gingival Crevicular Fluid In Stroke Survivors: A Pilot Study. - NormaliNormaliza Ab. Malik; Sa’ari Mohamad Yatim; Lijian Jin; Colman McGrath (Universiti Teknologi Mara (UiTM), 2024)
Indexed by MyCite